Analysis of Verstek's Verdict in Acts of Default on Credit Agreements Made by Debtors Against PT. BANK PAN Indonesia Tbk (Decision Study Number: 16/Pdt.G/2022/PN-Tjk) - Baharudin Baharudin; Okta Anita; Fadian Akbar Wisnugraha (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Banks are financial institutions whose main business is providing credit and services in payment traffic and money circulation, while the results of this study are the first factors that can cause defaults at PT. Bank Pan Indonesia Tbk Study Decision Number 16/Pdt.G/2022/PN-Tjk. due to negligence on the part of the debtor due to financial factors, factors of family problems or factors of work problems that make the debtor negligent in paying the credit, and secondly is the basis for the judge's consideration in imposing the Verstek Decision in default on the credit agreement committed by the debtor against PT. Bank Pan Indonesia Tbk Study Decision Number 16/Pdt.G/2022/PN-Tjk is in accordance with the legal sources in force in Indonesia, namely the Civil Code and Regulation voor de Buitengewesten, therefore the judge's consideration is appropriate and correct because it does not conflict with existing laws apply